(untitled) (Eurasian Scientific Herald, 2022)
This article analyzes the synergistic analysis of the properties of intuition in scientific cognition from a scientific philosophical point of view. In particular, the importance of rational and irrational cognitive concepts such as intuition, perception, imagination, attention, memory, perception, perception, and their synergistic analysis is highlighted.